Análise de dados multi-tabelas (COMDIM) para a avaliação de farinhas comestíveis por espectroscopia NIR e texturômetro - Farias, Letícia Caroline Dubinski de (2018)
Flours are products obtained from edible parts of one or more species of cereals, legumes, fruits, seeds, tubers and rhizomes by milling and / or other technological processes considered safe for food production. Wheat flour is the most technologically important flour in the food industry, as it is a major component of breads, biscuits, cakes and pastas. Gluten protein is responsible for the very desirable characteristics of wheat flour's extensibility and cohesiveness but is associated with celiac disease. In the search for flour to replace wheat flour, it is necessary to use traditional analytical techniques. Analytical methods employed for traditional flour analyzes involve timeconsuming techniques, using chemical reagents, as well as generating residues. In this way, the development of alternative methodologies for this purpose can bring benefits to industries, regulators, analysts, and consumers alike. This study proposes the use of spectroscopy in the near infrared (NIR) region associated to the multi-table analysis tool (ComDim) for the characterization of the flour in relation to the texture parameters identified by a texturometer. It was possible to infer about similarities and differences between the samples according to the absorption in the NIR region, as well as with respect to the texture parameters. Gluten-free meals: rice, brown rice, banana, sweet potatoes, eggplant, yacon, cassava starch, golden flax and açaí present characteristics similar to wheat flour, whole wheat and oats for adhesiveness, elasticity and cohesion. Gluten-free maize, white corn, brown flax, soybean, passion fruit peel, passion fruit, ginger, amaranth, chia, coconut, cassava and grapes have similar characteristics regarding hardness, gum, masticability and resilience. Gluten-free flours with specific texture characteristics may be an alternative for the formulation of food products, contributing to the quality of the final product, especially for the baking area.